Pemilihan Pangkalan Induk Skadron Pesawat Tempur TNI AU dengan Menggunakan Metode Analytical Hierarchy Process - Riano, Gagat; Pradhypta, Aura (Akademi Angkatan Udara, 2022)
Determining a location where the facility will be built is one of the important factors in the business and military planning process. Indonesia, as a country that has a large area, has problems in determining the right location to place its squadron of fighter aircraft in the national defense system. This study uses the Analytic Hierarchy Process (AHP) to solve this problem. There are five criteria considered in this study, namely deterrence strategy, counterbalance strategy, flight support facilities, base support facilities and the environment. This research is aimed at getting six out of 10 Indonesian Air Force air bases that meet the requirements to be placed in a squadron of fighter aircraft. The six air bases selected were SPO (15.17%), RSN (15.16%), HND (12.25%), HLM (12.16%), ABD (10.09%) and IWJ (10.07% ).